TRENDS IN THE DEVELOPMENT OF THE CORPORATE CULTURE OF A MODERN HIGHER EDUCATION INSTITUTION - Kirill B. Safonov (Russian Studies in Culture and Society)
The article examines the key features of the phenomenon of corporate culture of a higher educational institution. The importance of corporate culture as a system of values shared by all members of the team is noted. The practical significance of corporate culture in the activities of the university can be to increase the efficiency of scientific and pedagogical workers, all employees.